2017
DOI: 10.1038/s41598-017-02308-9
|View full text |Cite
|
Sign up to set email alerts
|

The relation between human hair follicle density and touch perception

Abstract: Unmyelinated low threshold C-tactile fibers moderate pleasant aspects of touch. These fibers respond optimally to stroking stimulation of the skin with slow velocities (1–10 cm/s). Low threshold mechanoreceptors are arranged around hair follicles in rodent skin. If valid also in humans, hair follicle density (HFD) may relate to the perceived pleasantness of stroking tactile stimulation. We conducted two studies that examined the relation between HFD and affective touch perception in humans. In total, 138 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 35 publications
4
26
0
Order By: Relevance
“…A large overlap was seen between modalities and intensities inducing pain and unpleasantness (Price, ) with no stimuli consistently perceived as unpleasant but not painful. There was no significant difference in pleasantness scores between stroking velocities; however, they did follow an inverted U ‐shape profile peaking at 1–3 cm/s, complement findings from studies from the forearm (Ackerley, Carlsson, et al, ; Jönsson et al, ; Loken et al, ; Luong et al, ).…”
Section: Discussionsupporting
confidence: 77%
“…A large overlap was seen between modalities and intensities inducing pain and unpleasantness (Price, ) with no stimuli consistently perceived as unpleasant but not painful. There was no significant difference in pleasantness scores between stroking velocities; however, they did follow an inverted U ‐shape profile peaking at 1–3 cm/s, complement findings from studies from the forearm (Ackerley, Carlsson, et al, ; Jönsson et al, ; Loken et al, ; Luong et al, ).…”
Section: Discussionsupporting
confidence: 77%
“…Body Hair: We hypothesise that the different body hair characteristics of the different participants had an overall impact on the perceived sensation. Previous research in affective touch already explored some of these relations between hair type and the perception [12]. During this experiment, we required participants to have enough hair on their arms, which limited our selection of participants to males.…”
Section: Discussionmentioning
confidence: 99%
“…Body Hair: In MAGHair, we elaborated on three different recipes and applied one of them to the forearm of different users. However, different users had a different type of hairs with different characteristics, such as density and length, which are likely to generate a different haptic sensation [12]. We encourage future research to focus on developing similar recipes and applying them to different types of body hair, such as the scalp hair, eyebrows, forearm, etc.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…Of note, CT afferents are found only in the hairy skin and hardly seen in the glabrous skin such as the palms. Interestingly, one report demonstrated that women had higher hair follicle density than men, and women rated affective touch stimuli as more pleasant and had higher tactile acuity . However, we cannot assess the innervation density of CT afferents due to lack of proper methods and we currently do not know whether CT afferents have functional difference among different parts of the body.…”
Section: Scratching Pleasurability and C Tactile Afferent Nerve Fibrementioning
confidence: 99%